El factor variabilitat a les constancies i configuracions perceptives. Aportacions experimentals - Ventura i Vall-llovera, C. (Universitat de Barcelona. Departament de Teoria i Història de l'Educació, 2009)
From the theoretical functional psychology model proposed by Roca (2006), the thesis aims to develop, experimentally, Variability factor within the field of perception, and also studies its effects in relation to other psychological factors or variables, such as Generalization, Practice and Contiguity.